The Effect of Profitability and Firm Size on Firm Value with Capital Structure as a Mediating Variable - Nyoman Cyntia Riesta UTAMI; I Made WIANTO; Ida Ayu SURASMI (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2025)
The property sector can withstand economic crises. The contribution of the property industry as one of the leading sectors to drive the Indonesian economy's GDP. However, historical performance still does not show significant improvement in the property sector. So it is necessary to research to analyze the factors that affect firm value. This study aims to analyze the effect of profitability, company size, and capital structure on firm value. The population in this study amounted to 91 companies, namely all property and real estate companies listed on the Indonesia Stock Exchange in 2024. While sampling in this study used purposive sampling so 13 companies were obtained with 6 years of observation the amount of data in the study was 78 observations. The analysis technique used to answer the hypothesis is path analysis using SPSS. The results of this study indicate that profitability has a negative but insignificant effect on capital structure, firm size has a positive and significant effect on capital structure in the company, profitability has a positive and significant effect on firm value, firm size has a positive but insignificant effect on firm value, capital structure has a negative but insignificant effect on firm value, capital structure does not act as a mediator on the effect of profitability on firm value, and capital structure acts as a perfect mediation on the effect of firm size on firm value in the company.